The Norwegian Tax Reform; Distributional Effects and the High-income Response - Karl Ove Aarbu; Thor Olav Thoresen (Statistics Norway, Research Department, 1997)
Are we better or worse off after the Norwegian tax reform of 1992 and how has the reform influenced the income sizes and the distribution of total income? This question denotes our twofold analysis in this paper. We first examine the trends in average income and income distribution in the period from 1991 to 1994. Second, we ask whether the tax reform can explain parts the observed income changes. Calculations from a tax-benefit model, assessing the direct distributional effect by applying post-reform tax rules on pre-reform data, do not predict any substantial increase in income inequality due to the tax reform of 1992. However, we find a significant post-reform increase in observed income inequality, while average income is about unaltered in the period. The increased inequality might be explained by the high income earners' response to large reductions in marginal tax rates. By applying panel data for 1991-1994 and a methodological approach developed by Feldstein (1995a), we find no evidence in support of significant behavioral responses due to decreased marginal tax rates on income. In fact, the overall elasticities are around zero, which differ substantially from Feldstein's estimate of 1.04, based on US-data. Other explanations, as the changes in the taxation of dividends, are discussed.
Keywords: D31; D63; H2; H31; 330; Tax reform; Income distribution; Social welfare; Personal tax